The Relationship Between Green HRM and Employee Green Creativity among Employees in Manufacturing Sector - Wong, Mei Jia; Wahab, Eta (Research in Management of Technology and Business, 2025)
There is less research conducted on how Green HRM can enhance green creativity in manufacturing sector. Therefore, this study aims to explore how employee green creativity can be enhanced by strengthening green human resource management. The objective of this study is to determine the level of Green HRM among employees in manufacturing sector, to determine the level of employee green creativity among employees in manufacturing sector, and to identify the relationship between Green HRM and employee green creativity among employees in manufacturing sector. This was a quantitative study by distributing an online survey to 384 employees in Selangor’s manufacturing sector with a response rate of 39.58%. The study’s data were analysed using both descriptive and correlation analysis with SPSS. The study found a significant positive relationship between Green HRM and employee green creativity, highlighting the potential for GHRM practices to drive sustainable innovation within employees of manufacturing sector.